Seedling Responses to Organically-Derived Plant Growth Promoters: An Effects-Based Approach - Hodge, Simon; Merfield, Charles N.; Liu, Wendy Y. Y.; Tan, Heng W. (Plants (Basel), 2021)
Organically-derived biofertilizers and biostimulants, developed from harvested materials such as seaweed and waste from animal and fish processing, are currently the subject of much fundamental and applied research. These products have significant potential in reducing synthetic fertilizer inputs to horticultural, arable, and pasture-based agricultural systems, although there is frequently some ambiguity over the magnitude and consistency of any positive effects these products may have on plant performance. This study examined the effects of organically-derived plant growth promoters (PGPs) available in New Zealand on the early vegetative growth of 16 plant species maintained under glasshouse conditions. When applied as a root drench to low nutrient potting mix, the effects of the PGPs on seedling shoot growth were strongly related to the NPK contents of the applied solutions. Any positive effects on shoot growth were, on average, reduced when the seedlings were maintained in higher nutrient growing media. Applying the PGPs at concentrations twice, and four times, the recommended concentration, only caused further growth responses when the PGPs contained high levels of nutrients. Applying the PGPs as a foliar spray had negligible effects on shoot growth. Overall, the results of these trials suggest that the positive effects of applying some organically-derived PGPs on seedling growth are a function of the PGP nutrient content, and not due to any indirect effects related to phytohormone pathways or modification of rhizosphere microorganisms.